What can be learnt from the effectiveness of Slovenia's anti-crisis state aid measures during the Great Recession - Burger, Anže (Teorija in praksa, 2020)
The aim of this article is to evaluate the impact of the anti-crisis state aid measures implemented in Slovenia between 2009 and 2015 to combat the Great Recession and use the insights gained to make an exante assessment of a series of fiscal relief and stimulus measures adopted by the Slovenian government during the first 6 months of the Covid-19 pandemic. We find that state aid for R&D, employment and training increased firm revenue and employment growth over a 5-year period, while the specialised anti-crisis measures and the rescue and restructuring state aid failed to improve the performance of subsidised firms. Our preliminary assessment of Slovenia%s Covid-19 fiscal policy response reveals that its size is exceptional compared to the previous recession and that the majority of the total fiscal stimulus was allocated through grants and allotted to individuals. Given the premium dividend the grants have shown in our empirical analysis of past anti-crisis state aid measures and findings from the literature on the fiscal multipliers, we expect the anti-corona fiscal policy actions to effectively mitigate the Covid-19 crisis' serious consequences in the short term.
Keywords: Covid-19; Crises; državne pomoči; Economic policy; Ekonomska politika; ekonomski ukrepi; Epidemics; Epidemije; Krize; protikoronski ukrepi; protikrizni ukrepi; rast podjetij; učinki protikriznih ukrepov